The effect of the training with the different combinations of frequency and peak-to-peak vibration displacement of whole-body vibration on the strength of knee flexors and extensors - Stania, M; Król, P; Sobota, G; Polak, A; Bacik, B; Juras, G (Biology of Sport, 2017)
Whole-body vibration training has become a popular method used in sports and physiotherapy. The study aimed to evaluate the effect of different vibration frequency and peak-to-peak displacement combinations on men knee flexors and extensors strength in isokinetic conditions. The sample consisted of 49 male subjects randomly allocated to seven comparative groups, six of which exercised on a vibration platform with parameters set individually for the groups. The experimental groups were exposed to vibrations 3 times a week for 4 weeks. The pre- and post- isokinetic strength tests, with the angular velocities of 240°/s and 30°/s, were recorded prior to and 2 days after the training. After 4 weeks of whole-body vibration training, a significant increase was noted regarding the mean values of peak torque, average peak torque and total work for knee flexors at high angular velocity in Groups I (60 Hz/ 4 mm) and V (40 Hz/ 2 mm) (p<0.05). The mean percentage values of post-training changes to study parameters suggest that the training had the most beneficial effect in Groups I (60 Hz/4 mm) and IV (60 Hz/2 mm) (p<0.05). Whole-body vibrations during static exercise beneficially affected knee flexor strength profile in young men at high angular velocity. The combinations of 60 Hz/4 mm seem to have the most advantageous effects on muscle strength parameters.